NOVEL APPROACH OF AUTOMATIC DISEASE PREDICTION AND REGULAR CHECK-UP SYSTEM USING ML/DL - DR. NILESH SABLE, SAYALI VIJAY GHODKE, ARTI SIKHWAL, (Design Engineering, 2021)
The important objective of this system is to provide an accurate prediction of disease like Pneumonia, Fungal Infection, AIDS, Migraine, Jaundice, Common Cold, Heart Attack, Acne, COVID-19, etc. This system will also give the regular check-up report of the user. As the doctor may not be available always when needed, but in the modern time scenario, according to necessity one can always use this prediction and regular check-up system anytime. The main aim of our project is to analyze the disease without causing harm to humans. We will be using symptoms of the user as well as the current image and video from the user, and by this way this system becomes useful in prediction of diseases at their initial stages.